2002
DOI: 10.1081/ss-120005662
|View full text |Cite
|
Sign up to set email alerts
|

Water Defluoridation by Mexican Heulandite–clinoptilolite

Abstract: Fluorosis is caused by excess ingestion of fluoride. In this work, a natural Mexican zeolite (heulandite -clinoptilolite from Sonora) was evaluated for the sorption of fluoride ions from aqueous solutions and well-water. The effects of sodium, calcium, lanthanum, and europium in the crystalline network of this aluminosilicate, as well as, the effects of pH and particle size of the zeolite on the fluoride sorption were determined. It was found by x-ray diffraction, electronic microscopy, and IR that the structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
12
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 15 publications
8
12
0
2
Order By: Relevance
“…Comparison of these micrographs before and after fluoride sorption shows that there is no significant change in the morphology of the surface of the resins, as the concentrations of fluoride for the experimental study were very low. Similar results were observed by DiazNava et al [41]. …”
Section: Characterization Of Ierssupporting
confidence: 91%
“…Comparison of these micrographs before and after fluoride sorption shows that there is no significant change in the morphology of the surface of the resins, as the concentrations of fluoride for the experimental study were very low. Similar results were observed by DiazNava et al [41]. …”
Section: Characterization Of Ierssupporting
confidence: 91%
“…The city is located in northern Mexico, a region that has fluoride concentrations higher than the National and EPA's standards [2]. Analysis indicated that the groundwater has an average fluoride concentration of 6.95 mg/L.…”
Section: Validation Of Adsorption Kinetic Model With a Mexican Groundmentioning
confidence: 99%
“…Excessive fluoride in groundwater is also found in many regions worldwide. Many groundwater wells in the North-central part of Mexico contain fluoride in concentrations higher than 6 mg/L [2]. The maximum contaminant level (MCL) in drinking water in USA is 4.0 mg/L according to the drinking water standards set by the US Environmental Protection Agency, and the maximum acceptable concentration of fluoride in drinking water established by the World Health Organization is 1.5 mg/L.…”
Section: Introductionmentioning
confidence: 99%
“…Many natural adsorbent materials were tried in the past to find out efficient and economically viable defluoridating agents such as activated alumina (Ghorai and Pant 2005), alumina-gibbsite (Mariappan et al 2003), activated carbon (Karthikeyan and Ilango 2007), calcite (Turner et al 2010), clay (Coetzee et al 2003), zeolite (Díaz-Nava et al 2007), activated charcoal (Daifullah et al 2007), bleaching earth (Mahramanlioglu et al 2002), red mud (Tor et al 2009), brick powder (Yadav et al 2006), sugarcane charcoal , waste tea ash (Mondal et al 2012a) and rice husk ash (Mondal et al 2012b).…”
Section: Introductionmentioning
confidence: 99%